Chemicals pofile of Kelakai leaves extracts (Stenochlaena palustris) with antioxidant and antibacterial activity against Aeromonas hydrophila - Fatmawati,; Noor Arida Fauzana,; Siti Aisiah,; Ririen Kartika Rini,; Olga,; Tanod, Wendy Alexander; Riyadi, Putut Har (Penerbit Universiti Kebangsaan Malaysia, 2022)
Kelakai (Stenochlaena palustris) is a typical Kalimantan plant that has been used by Banjar and Dayak communities as traditional medicine and vegetable. This study aimed to examine the potential of kelakai leaves extracts as a natural product to inhibit Aeromonas hydrophila growth. This research included kelakai leaves sampling in Banjarbaru, South Kalimantan, Indonesia, extraction (EtOH 1:4 w/v), phytochemical and chemicals profile screening (LCMS), prediction of biological activity (PASS server), antibacterial activity (broth dilution), antioxidant activity (DPPH), total phenol (gallic acid equivalent), total flavonoid (quercetin equivalent), and total alkaloid (caffeine equivalent). The phytochemical screening showed that the kelakai leaves extract contained saponins, tannins, phenolics, flavonoids, alkaloids, anthraquinones, triterpenoids, and steroids. The chemicals profile of the kelakai leaves ethanol extract consisting of alkaloids, alcohols, amines, amine alcohols, amino acids, fatty acids, flavonoids, glycosylglucose, lipid derivatives, monocarboxylic acid, saponins, steroids, and terpenoids. Prediction of biological activity showed kelakai leaves extract an inhibitor of the peptidoglycan glycosyltransferase enzyme and free radical scavenger. The antibacterial assay showed that kelakai leaves extract could inhibit the growth of A. hydrophila. In addition, kelakai leaves extract showed very strong antioxidant potential (IC50 42.47 ± 0.98 µg/mL), with a total phenol content of 193.97 ± 0.11 mg GAE/g, total flavonoid 23.45 ± 0.14 mg QE/g, and total alkaloid 11.74 ± 0.10 mg CE/g. These research findings show that the ethanol extract of kelakai leaves could be antibacterial against A. hydrophila, which is closely related to its antioxidant properties.